Cancer survivors on the process of returning to work: a Danish focus group study - Anne F Nielsen; Line Zinckernage; Jan B Tofte; Helle Timm (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: The aim of this study was to explore Danish cancer survivors perspectives on the process of returning to work. METHODS: Six focus-group interviews (N=32) were held with cancer survivors attending a five-day rehabilitation stay. Data were analyzed by applying meaning condensation then organized into themes. RESULTS: Most cancer survivors do not imagine themselves resuming work in the same way as before they had cancer. Many cancer survivors are missing support when navigating the bureaucracy involved with the process of returning to work and do not know how to become, or when they will be, ready for work. CONCLUSIONS: Practice guidelines that support Danish cancer survivors in returning to work are currently based on knowledge from international reviews but should be supplemented with elements addressing how and when to become ready for work.